[OP.7B.02] METABOLIC SYNDROME IS ASSOCIATED WITH INCREASED SYMPATHETIC NERVOUS SYSTEM ACTIVITY AND ARTERIAL STIFFNESS IN RESISTANT HYPERTENSIVE PATIENTS. (September 2016) - Dimitriadis, K.; Tsioufis, C.; Andrikou, E.; Kasiakogias, A.; Kyriazopoulos, K.; Frantzeskakis, A.; Kalos, T.; Liatakis, I.; Koutra, E.; Tousoulis, D.
Abstract : Objective: Resistant hypertension is related to sympathetic overdrive and arterial stiffening, while there are scarce data whether metabolic syndrome further potentiates sympathetic activity and vascular abnormalities in this setting. The aim of this study was to assess the effect of the metabolic syndrome on muscle sympathetic nerve activity (MSNA) and arterial stiffness in resistant hypertensive patients. Design and method: We studied 36 patients with resistant hypertension [age: 59 ± 10 years, 24 males, office blood pressure (BP): 178/93 ± 14/11 mmHg, 24-hour BP: 146/84 ± 13/11 mmHg, under 4.3 ± 0.6 drugs] that underwent transthoracic echocardiographic study and blood sampling for assessment of the metabolic profile. Metabolic syndrome was defined according to the Adult Treatment Panel III criteria and arterial stiffness was evaluated on the basis of carotid to femoral pulse wave velocity (PWV). In all participants sympathetic drive was assessed by MSNA estimations based on established methodology (microneurography). Results: Resistant hypertensive patients with metabolic syndrome (n = 16) compared to those without (n = 20) exhibited higher waist circumference (109.2 ± 5.3 vs 94.8 ± 9.1 cm, p = 0.001), fasting glucose (130.9 ± 2.2 vs 94.3 ± 2.2 mg/dl, p < 0.05), office systolic BP (185 ± 16 vs 170 ± 13 mmHg, p < 0.001) and left ventricular mass index (132.2 ± 17.1 vs 123.6 ± 16.2 g/m 2, p = 0.001). Moreover, metabolic syndrome 2 patients compared to those without were characterized by greater levels of carotid to femoral PWV (11.8 ± 0.7 vs 9.2 ± 0.9 m/sec, p < 0.001) and sympathetic nerve traffic as reflected by MSNA levels (82.1 ± 2.5 vs 73.3 ± 2.1 bursts per 100 heart beats, p < 0.001). In all participants MSNA was related to waist circumference (r = 0.36, p = 0.004) and office systolic BP levels (r = 0.36, p < 0.05) but there was no association with PWV values (p = NS). Conclusions: In resistant hypertensive patients, metabolic syndrome is associated with high MSNA and PWV levels. These findings support that metabolic syndrome further deteriorates sympathetic activity and arterial stiffening characterizing resistant hypertension.